Upaya peningkatan pengetahuan ibu hamil tentang pertumbuhan janin - Anita Rahmawati; Endah Marianingsih Theresia (Poltekkes Kemenkes Yogyakarta, 2020)
One of the causes of the low level of knowledge of mothers during pregnancy is the lack of counseling, information, and education (IEC). In this case, midwives are required to be able to provide information about how the fetus grows during pregnancy. Pregnancy cards are small cards consisting of several sheets of paper that have been bound and which contain the knowledge of fetal growth from 4 weeks to 40 weeks. This pregnancy card is printed and made so that pregnant women will be interested and will be happy to read it. The expectation of giving a pregnancy card to pregnant women is that pregnant women will know the stages of fetal growth so that pregnant women will be able to provide appropriate stimulation following the stages of growth. In connection with these conditions, counseling needs to be done to as many as 30 pregnant women about fetal growth using the Pregnancy Card. The implementation of this activity is in September and October 2019. The facilities needed are the Pregnancy Card, a questionnaire for the pre and post-test. From the results of the evaluation after the post-test, the results obtained with an average value of 80. Based on the results of the activity it can be concluded that the community service activities are carried out well, evidenced there is an increase from pre to post-test, and pregnant women become aware of fetal growth in pregnant women.